Extraction and characterization of cellulose nanocrystals from nata de coco (Komagataeibacter xylinus): Effect of acid treatments and its application as coating in delaying the decay of ripe banana - Bayog, Mc John Paul R. (Animo Repository, 2024)
Nata de coco or bacterial cellulose (BC) is a sustainable material that needs to be explored for novel applications. Converting the bacterial cellulose into a stable suspension of cellulose nanocrystals (CNC) adds a novel functionality to the material. This work explores the preparation of CNCs from BC using the two least used mineral acids in the hydrolysis process: hydrobromic acid and nitric acid. The objective of this work is to compare the physical and thermal properties of CNCs prepared from these two different acids and explore a novel application as an edible coating to extend the shelf life of bananas. HBr-CNC and HNO3-CNC extractions afforded CNC yields of 0.262%, and 0.374%, respectively. The physicochemical analyses of both CNCs are fairly similar with slight deviations in TEM and DSC results. The HBr extracted CNCs had an average length of 315.87(±81.84) nm and an average diameter of 21.38(±2.80) nm compared to the CNCs extracted using HNO3, which recorded an average length and diameter of 363.04(±179.91) nm and 20.32(±4.83) nm, respectively. DSC results showed deviation in the degradation temperatures of the CNCs where the HBr-CNCs degraded at about 281.7°C, while the HNO3-CNCs showed more stability, degrading at 354.6 °C. TGA analysis revealed improved thermal stability for CNCs, with higher onset degradation temperatures (HBr-CNC: 335°C; HNO3-CNC: 340°C) compared to raw cellulose. The CNC-based coating was successful in prolonging the shelf-life of banana samples.